(untitled) (Revista INTEREDU11, 2021)
This article discusses the progress and challenges faced by Peruvian state educational measures regarding the reparation and inclusion of Afro-Peruvian peoples in education sector policies. A brief historical bibliographical review of the measures of Afro-Peruvian inclusion in educational policies is made and through a mapping of the graphic representation and content in relation to the Afro-Peruvian people in the state textbooks of secondary education, the content distributed in the books of DPCC, Mathematics, Communication and Science and Technology from 1st to 5th grade of secondary school is analyzed. It is evident that, on the one hand, an important visibility of the Afro-Peruvian movement has been gained in the curricula, however, even the educational textbooks reflect a Peruvian multiculturalist vision that continues to fetishize and encapsulate the Afro-Peruvian population in certain socio-cultural contexts and spaces of development. The Peruvian government is challenged to think of Peruvian society in Afro-Peruvian terms, integrating their contributions in a cross-cutting manner and not only in ethnic-racial niches.